Caracterização de óxidos nanoestruturados através de espectroscopia Raman em condições de pressões elevadas - Silva, Antônio Neves da (2015)
Raman spectroscopy studies has been used to investigate the structural properties of nanocasted oxides, CeO2 (Ce), ZrO2 (Zr), TiO2 (Ti), SnO2 (Sn), MnOx (Mn), CeO2−Al2O3 (CeAl), CeO2−MnO2 (CeMn) and NiO−Al2O3 (NiAl), obtained from nanocasting technique. The studies were collaborated by Transmission Electron Microscopy (TEM) and Infrared Spectroscopy with Fourier transform (FT-IR) techniques. The results suggested that Ce, Sn and Mn monoxides have structural defects (vacancies) derived from the preparation method of the solids. This result is indeed not common for ordinary oxides. At room pressure Ti anatase is tetragonal belonging to D4h19 (I41/amd) space group and changes for the monoclinic phase at pressures around 14 GPa. With pressure release Ti changes to orthorhombic phase. The sample Mn showed a phase transition at about 17,5 GPa, whose phase is still unknown. For all samples the spectra appear strongly influenced by the particle size, shape and structure of the material, especially in the position value of pression for phase transition. The Ce, Zr and Sn remained stable up to the maximum pressure achieved and Ti and Mn showed phase transition. TEM analysis estimated the average nanoparticle size of 9 nm (Ce), 34 nm (Sn), 54 nm (Mn), 10 nm (CeMn) and 8 nm (CeAl); and distance between crystallographic planes of d111 = 0,3 nm (Ce), d110 = 0,33 nm (Sn), d111 = 0,36 nm (Mn), d111 = 0,32 nm (CeMn) e d111 = 0,3 nm (CeAl). The nanoparticles sizes for Ce, CeMn and CeAl, obtained from Raman spectroscopy data were 7, 8 and 3 nm, respectively, wich agree well with the results of TEM. The images suggest that all the nanoparticles were distributed over the remaining silica surface. All nanoparticles were agglomerated in some regions, due to the fact that in the silica-based nanocomposites, calcination leads to migration to nucleation sites. The FT-IR spectra indicated the presence of modes related to vibrations of OH bonds in na- nostructures; and the vibrations of Ce-O, Sn-O and Mn-O bonds of Ce, Sn and Mn oxides, respectively. The spectra of sample CeMn showed that the interaction between Mn and Ce can break the structure of the fluorite type and form oxygen vacancies in the Ce structure whereas the CeMn and NiAl high pressure results showed line broadening, decreasing in modes intensity and remained stable until the maximum pressure value reached, 14 and 18 GPa respectively. The stability of CeAl was maintained up to 36 GPa, in contrast with that observed for Ce monoxide, in which a phase transition occurs at about 35 GPa to a structure of PbCl2 orthorhombic (space group D2h16). The introduction of oxide Al2O3 in the structure of CeO2 increases the stability of this structure. The effect of varying laser power incident in nanostructured oxides showed an increase in intensity in all nano oxides spectra with the increasing laser power. Mn oxide, in particular, presented an increase in the modes related to defects due to vacancies generated by OH removing.